Impact of having realistic tropical cyclone frequency on ocean heat content and transport forecasts in a high‐resolution coupled model. Issue 14 (16th July 2015) - Zhang, S.; Zhao, M.; Lin, S.‐J.; Yang, X.; Anderson, W.; Zhang, W.; Rosati, A.; Underwood, S.; Zeng, F.
Abstract This study examines two sets of high‐resolution coupled model forecasts starting from no‐tropical cyclone (TC) and correct‐TC‐statistics initial conditions to understand the role of TC events on climate prediction. While the model with no‐TC initial conditions can quickly spin‐up TCs within a week, the initial conditions with a corrected TC distribution can produce more accurate forecast of sea surface temperature up to 1.5 months and maintain larger ocean heat content up to 6 months due to enhanced mixing from continuous interactions between initialized and forecasted TCs and the evolving ocean states. The TC‐enhanced tropical ocean mixing strengthens the meridional heat transport in the Southern Hemisphere driven primarily by Southern Ocean surface Ekman fluxes but weakens the Northern Hemisphere poleward transport in this model. This study suggests a future plausible initialization procedure for seamless weather‐climate prediction when individual convection‐permitting cyclone initialization is incorporated into this TC‐statistics‐permitting framework.